The recovery of India: economic growth in the Nehru era - Balakrishnan, Pulapre (2007)
This paper investigates the relationship between the policy regime and growth during 1950-64, termed here "the Nehru era". While there exist valuable early appraisals of the period, access to new data and fresh information allows for a longer and more comparative view of the outcome. We find overwhelming evidence not only of resurgent growth, but also of a lasting transformation of a stagnant colonial enclave into an economy capable of sustained growth. It is useful to recognise the economic policy of this period as distinct, not only from what preceded it but also from what came after, for it facilitates an understanding of the political conditions needed for economic interventions that are growth inducing. The paper also addresses some lingering perceptions of policy of the time, notably its impact on agriculture and the governance of the public enterprises. - Reproduced.
Keywords: Economic growth - India; Economic growth